2019
DOI: 10.3389/fphys.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Temporal Causal Links and the Differences by Sport or Lack Thereof

Abstract: Fitness level, fatigue and adaptation are important factors for determining the optimal training schedule and predicting future performance. We think that adding analysis of the mutual relationships between cardiac and respiratory activity enables better athlete profiling and feedback for improving training. Therefore, the main objectives were (1) to apply several methods for temporal causality analysis to cardiorespiratory data; (2) to establish causal links between the signals; and (3) to determine how param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…Thus, coaches and sport practitioners should be aware that changes in the respiratory rate may confound spectral indices [ 53 ]. It has been suggested that depth of breathing could be even more important than its rate [ 5 ]. Młyńczak and Krysztofiak proposed cardiorespiratory temporal causal links with the path for lying supine from tidal volume, through heart activity variation and average heart activity, to respiratory timing [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, coaches and sport practitioners should be aware that changes in the respiratory rate may confound spectral indices [ 53 ]. It has been suggested that depth of breathing could be even more important than its rate [ 5 ]. Młyńczak and Krysztofiak proposed cardiorespiratory temporal causal links with the path for lying supine from tidal volume, through heart activity variation and average heart activity, to respiratory timing [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that depth of breathing could be even more important than its rate [ 5 ]. Młyńczak and Krysztofiak proposed cardiorespiratory temporal causal links with the path for lying supine from tidal volume, through heart activity variation and average heart activity, to respiratory timing [ 5 ]. Even if those links appeared rather moderate, the possible differences in the respiratory pattern should be taken into account in the protocol assessing the cardiac parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early data suggest that physical training changes patterns of cardiorespiratory interaction. Mlynczak and Krysztofiak (2019) used a Granger causality framework that parameterized cardiorespiratory causal link structures and directions to distinguish athletes from non-athletes at rest with 83% accuracy. Increased cardiorespiratory coordination after training has also been shown (Balagué et al, 2016).…”
Section: Introductionmentioning
confidence: 99%